# Answer to Question #11040 in Algebra for n k siva prasad

Question #11040

factorize

(x-y+z)^2+2(x-y+z)(y-z+x)+(y-z-x)

(x-y+z)^2+2(x-y+z)(y-z+x)+(y-z-x)

Expert's answer

factorize

(x-y+z)^2+2(x-y+z)(y-z+x)+(y-z-x)=(x-y+z)*(x-y+z+2y-2z+2x)-(x-y+z)=(x-y+z)*(y-z+3x-1)=(x-y+z)(3x+y-z-1)

(x-y+z)^2+2(x-y+z)(y-z+x)+(y-z-x)=(x-y+z)*(x-y+z+2y-2z+2x)-(x-y+z)=(x-y+z)*(y-z+3x-1)=(x-y+z)(3x+y-z-1)

Need a fast expert's response?

Submit orderand get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

## Comments

## Leave a comment